Effect of Meloidogyne sp. on growth and yield of tomato. - Salazar-Antón, Wilber (2013)
The objective of this work was to determinate therelationship between initial density and final density ofMeloidogyne sp in tomato crop. The study was carried out atLeón, Nicaragua during 2011. The variables measured werenumber of nematodes at transplant, number of nematodesat harvest time, height at maturity of plants and yield inkilograms. Nematode extraction was performed through theBaermann modified method. In the study, the initial density(Pi) showed a positive linear correlation with the final density(Pf). However, it was observed that when Pi was equal to400 nematodes/100 g of soil, the reproduction factor wasincreased to 3.64, on the contrary, when Pi was equal to 700nematodes/100 g of soil, reproduction factor was reduced to2.48. Pi was inversely correlated to weight of tomato fruitsand height of plants. Plants with 200 nematodes/100 g of soilhad fruit weight 2.19 kg and height 153.20 cm compared to0.93 kg and 135.24 cm in plants with 600 nematodes/100g of soil. There was a positive correlation between Pi andPf of Meloidogyne sp. in tomatoes. The populations of thisnematode, were inversely correlated with plant height andfruits weight.